Influence of particle size on the magnetic and microwave absorption properties of magnetite via mechano-mechanical methods for micro-nano-spheres - Elmahaishi, Madiha Fathi; Azis, Raba'ah Syahidah; Ismail, Ismayadi; Matori, Khamirul Amin; Muhammad, Farah Diana (Elsevier, 2024)
The demand for innovative electromagnetic wave absorbers stems from the pressing need to mitigate electromagnetic interference and pollution emanating from electronic devices and communication technologies, which pose risks to human health and disrupt the functionality of electronic equipment. This study investigates how particle size influences the magnetic and microwave absorption properties of magnetite micron-nano-spheres. Utilizing ball milling (BM) and mechanochemical alloying (MA), particle sizes were controlled by varying the milling times, resulting in a reduction of magnetite's average particle size from 3 µm to 43 nm. The research uncovers the unique effects of blending micron and nano-sized particles, a phenomenon previously undocumented. It was observed that saturation magnetization and coercivity increase with larger particle sizes due to the small size effect. The complex permittivity, dielectric loss and attenuation constant of the magnetite nanocomposites were influenced by the larger interface area and increased defects in smaller-sized nano-filler composites. Decreasing the magnetite particle size leads to a lower frequency shift and a broader bandwidth of the reflection loss (RL) peak in the fixed absorber, with maximum RL achieved for thinner absorber layers. Notably, the mixed micron-nano magnetite composite exhibits promising microwave absorption capabilities, achieving a maximum RL of −35.36 dB at 16.8 GHz with a 1 mm thickness, making it suitable for lightweight microwave absorption. Resonance frequencies corresponding to RL below −20 dB extend to 3.63 GHz, meeting the 99 % wave absorption requirement due to the high loss tangent of antiferromagnetic resonance and significant magnetic relaxation peak over the 8–18 GHz frequency range. This study underscores the significant impact of adjusting the particle size on microwave absorption properties, where decreasing the size broadens the absorption bandwidth, shifts the RL peak to lower frequencies and maximizes RL with thinner thicknesses. Increasing the nano-filler content enhances the absorption bandwidth and microwave absorber performance by augmenting the dielectric loss, attenuation constant and impedance matching. Overall, controlling the particle size proves effective in tailoring microwave absorption, highlighting the potential of magnetite composites as ultra-thin, lightweight materials capable of absorbing a wide range of microwave frequencies. These composites find applications in microwave absorption, stealth technology and managing electromagnetic interference, leveraging the magnetic properties of ferrites and exploiting super-exchange interactions in microparticles-sized materials. Moreover, they benefit from the amplified dielectric or/magnetic losses resulting from the characteristics of nanoparticle-sized materials, including high surface area, greater surface atoms and multiple reflections, resulting in exceptional microwave absorption performance exceeding 99 % across an exceptionally broad bandwidth.